Numerical Solution of Linear Integral Equations Using Modified Block Pulse Functions - Ahmad, Ayyubi (Proceeding International Conference on Religion, Science and Education, 2022)
A computational method based on modified block pulse functions is proposed for solving numerically the linear Volterra and Fredholm integral equations. We obtain integration operational matrix of modified block pulse functions on interval .A modified block pulse functions and their integration operational matrix can be reduced to a linear upper triangular system.Then, the problem under study is transformed to a system of linear algebraic equations which can be used to obtain an approximate solution of linear Volterra and Fredholm integral equations.Furthermore, the rate of convergence is and error analysis of the proposed method are investigated. The results show that the approximate solutions have a good of efficiency and accuracy.